Hydrotoolbox, a package for hydrometeorological data management - Toum, Jorge Ezequiel (2023)
The hydrometeorological data provided by federal agencies, research groups and private companies are heterogeneous: records are kept in different formats, quality control processes are not the same and may even vary within a given agency, variables are not always recorded with the same temporal resolution, there are data gaps and doubtful values. Once these problems are dealt with, it is useful to have tools to safely store and manipulate the series, providing temporal aggregation, dynamic visualization for analysis, static graphics to publish and/or communicate results, techniques to correct and/or modify the series, among others. Here we introduce a package written in the R language using object-oriented programming and designed to accomplish these objectives, giving to the user a general framework to work with any kind of  hydrometeorological series. We present the package design, its strengths, limitations and show its application for two real cases.